2007
DOI: 10.1037/0012-1649.43.6.1360
|View full text |Cite
|
Sign up to set email alerts
|

Six-week postpartum maternal self-criticism and dependency and 4-month mother-infant self- and interactive contingencies.

Abstract: Associations of 6-week postpartum maternal self-criticism and dependency with 4-month mother-infant self- and interactive contingencies during face-to-face play were investigated in 126 dyads. Infant and mother face, gaze, touch, and vocal quality were coded second by second from split-screen videotape. Self- and interactive contingencies were defined as auto- and lagged cross-correlation, respectively, using multilevel time-series models. Statistical significance was defined as p<.05. Regarding self-contingen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
124
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(136 citation statements)
references
References 89 publications
10
124
0
1
Order By: Relevance
“…With maternal depression, selfcontingency was lowered for mothers and infants. This is an important finding, consistent with Beebe et al (2007). Lower self-contingency makes it harder for each individual to anticipate one's own and the partner's ongoing behavioral stream.…”
Section: The Optimal Midrange Model Of Self-and Interactive Regulationsupporting
confidence: 73%
See 3 more Smart Citations
“…With maternal depression, selfcontingency was lowered for mothers and infants. This is an important finding, consistent with Beebe et al (2007). Lower self-contingency makes it harder for each individual to anticipate one's own and the partner's ongoing behavioral stream.…”
Section: The Optimal Midrange Model Of Self-and Interactive Regulationsupporting
confidence: 73%
“…Hane, Feldstein, and Dernetz (2003) found that midrange vocal coordination was related to higher maternal sensitivity at 4 months. Beebe et al (2007) found that 6-week self-criticism was associated at 4 months with heightened maternal interactive contingencies (in some modalities) and lowered (in others); but self-contingency was lowered.…”
Section: The Optimum Midrange Model Of Interactive Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…From a clinical perspective, in treatment one might seek to augment the dependent mother's ability to experience feelings of love toward her baby, feelings that could function as a buffer in a period of suffering and pain. Self-critical mothers, in contrast, seem to need assistance in overcoming their inability to experience feelings of love because of their feelings of guilt, shame, and anger-feelings that contribute to their tendency to disengage from their infant and from their sources of interpersonal support because of their avoidant coping style (Beebe et al, 2007).…”
Section: Further Studies On the Two Configurations Modelmentioning
confidence: 99%